TDR Technique for Estimating the Intensity of Evapotranspiration of Turfgrasses - Grzegorz Janik; Karol Wolski; Anna Daniel; Małgorzata Albert; Wojciech Skierucha; Andrzej Wilczek; Paweł Szyszkowski; Amadeusz Walczak (The Scientific World Journal)
The paper presents a method for precise estimation of evapotranspiration of selected turfgrass species. The evapotranspiration functions, whose domains are only two relatively easy to measure parameters, were developed separately for each of the grass species. Those parameters are the temperature and the volumetric moisture of soil at the depth of 2.5 cm. Evapotranspiration has the character of a modified logistic function with empirical parameters. It assumes the form ETRθ2.5 cm,T2.5 cm=A/1+B·e-C·θ2.5 cm·T2.5 cm, where: ETRθ2.5 cm,T2.5 cm is evapotranspiration [mm·h−1], θ2.5 cm is volumetric moisture of soil at the depth of 2.5 cm [m3·m−3], T2.5 cm is soil temperature at the depth of 2.5 cm [°C], and A, B, and C are empirical coefficients calculated individually for each of the grass species [mm·h1], and [—], [(m3·m−3·°C)−1]. The values of evapotranspiration calculated on the basis of the presented function can be used as input data for the design of systems for the automatic control of irrigation systems ensuring optimum moisture conditions in the active layer of lawn swards.